Measuring the Impact of COVID-19 on Young Adult Functional Capacity: A Comparative Study of Walking and Step Endurance Tests - Patchareeya Amput; Arunrat Srithawong; Sinthuporn Maharan; Puttipong Poncumhak; Patcharin Phrompao; Eakarach Wongsaya; Tichanon Promsrisuk; Sahachat Aueyingsak (Physical Education Theory and Methodology)
Objectives. This study aimed to evaluate and compare the functional capacity of young adults recovering from COVID-19 using the 6-Minute Walk Test (6MWT) and 2-Minute Step Test (2MST), focusing on cardiovascular parameters, and to examine correlations between these tests, demographic factors, and muscle strength.